Environment variables affect CPUE and spatial distribution of fishing grounds on the light falling gear fishery in the northwest Indian Ocean at different time scales - Han, Haibin; Yang, Chao; Zhang, Heng; Fang, Zhou; Jiang, Bohui; Su, Bing; Sui, Jianghua; Yan, Yunzhi; Xiang, Delong (Frontiers in Marine Science, 2022)
To better develop and protect the pelagic fishery in the northwestern Indian Ocean, China's fishery enterprises have been producing pelagic fishery in the northwest Indian Ocean for a long time. Based on the fishing log data of light falling gear in the northwest Indian Ocean from 2016 to 2020, this study analyzed the impact of different time scales on the catch rate and fishing ground center of gravity of light falling gear fishing ground. We also explored the relationship between different time scales and catch per unit effort (CPUE) by using the fishing ground center of gravity, Random Forest model (RF), and generalized additive model (GAM). The results were shown as follows: (1) From 2016 to 2020, 76576t were captured, and 16496 nets were operated; (2)The gravity center of fishing ground in the Northwest Indian Ocean moved to the northeast as a whole, and the monthly fishing ground gravity center changed first to the Southern and then to the northern; (3) RF model (R² =0.709, RMSE = 0.2034 and prediction accuracy is 55.8%), which is better than GAM model (R² = 0.632, RMSE = 0.2242, and prediction accuracy is 37.3%). In the RF model, the importance of time variables on CPUE was in the order of week, year, operation time, and lunar phase; In the GAM model, were week, year, lunar phase, and operation time. On the whole, the importance of the long time scale (year, week) is greater than that of the short time scale (lunar phase and operation time). (4) RF model and GAM model show that the most critical environmental variables were SST, DO, SSS and Chla, and the least important were SSH, ∆50, and CV50. SST, Chla, and DO significantly impact pelagic fishery and CPUE and are critical reference indexes for predicting the Northwest Indian Ocean light is falling gear fishing ground. (5)The 95% confidence interval showed that the suitable interval of time, space, and environmental variables in the RF model was much smaller than in the GAM model.